On Line Learning In Vocational School at Bekasi - Hanggono Arie Prabowo (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study was to determine the effect of online learning on entrepreneurship learning of vocational school students in the city of Bekasi. The research focus of the program used was the Google Classroom and Quiziz programs. The research method used is a quantitative method. The research object was the students of SMK Insan and Dreiwanti Bekasi City. The total population of 270 students, a sample of 56 students of class XI. Before being processed, the data would be tested classically. The classical test included the reliability test and multicollinearity test results and multiple linear degression tests. After the classical test, the data were processed with the SPSS 20 program. The results showed that the Google classroom on the effect of entrepreneurial learning outcomes, there was no effect of quiziz on entrepreneurial learning outcomes, and there was an effect of google classroom and quiziz simultaneously on entrepreneurial learning outcomes. It was better if teachers and students could optimize online learning again, by using other applications such as you tube, google meeting and others. For teachers and students who had not mastered this technology, online training should be provided, so that learning could run smoothly without encountering obstacles.